Electrical potential difference during laser welding. (25th July 2014) - Zohm, H.; Ambrosy, G.; Lackner, K.
Abstract : We present a new model for the generation of thermoelectric currents during laser welding, taking into account sheath effects at both contact points as well as the potential drop within the quasi-neutral plasma generated by the laser. We show that the model is in good agreement with experimentally measured electric potential difference between the hot and the cold parts of the welded workpiece. In particular, all three elements of the model are needed to correctly reproduce the sign of the measured voltage difference. The mechanism proposed relies on the temperature dependence of the electron flux from the plasma to the workpiece and hence does not need thermoemission from the workpiece surface to explain the experimentally observed sign and magnitude of the potential drop.